Optimizing ankle performance when taped: Effects of kinesiology and athletic taping on proprioception in full weight-bearing stance. Issue 3 (March 2017) - Long, Zhi; Wang, Renwei; Han, Jia; Waddington, Gordon; Adams, Roger; Anson, Judith
Abstract: Objectives: To explore the effects of kinesiology taping (KT) and athletic taping (AT) on ankle proprioception when tested in functional, full weight-bearing stance. Design: Cross-sectional study. Methods: Twenty-four healthy university students participated. Proprioception was measured using the Active Movement Extent Discrimination Apparatus (AMEDA). The three testing conditions: no-taping, KT, AT, and foot tested were randomly assigned. Perceived comfort, support and proprioceptive performance under two taping conditions were recorded. Results: Proprioceptive discrimination scores with 95% CIs for no-taping, KT and AT were 0.81 (0.79–0.84), 0.81 (0.79–0.83), and 0.79 (0.77–0.81). Repeated measures ANOVA showed neither any significant difference associated with taping compared with no-taping (p = 0.30), nor any difference between KT and AT (p = 0.19). The group was then divided, according to their no-taping scores, into two sub-groups: with scores below the no-taping mean (n = 13), and above the mean (n = 11). ANOVA revealed a significant interaction (p = 0.008) indicating that above-average no-taping performers proprioception scores were worse when taped, whereas below-average performers improved. For both KT and AT, only ratings of perceived comfort when taped were significantly associated with actual proprioceptive performance (both r > 0.44, p ≤ 0.03). Other perception ratings (support and performance) were significantly inter-correlated (both r > 0.42, p < 0.04), but neither was significantly correlated with actual performance (both p > 0.31). Conclusions: Taping of the foot and ankle may amplify sensory input in a way that enhances proprioception of poor performers but produces an input overload that impairs proprioception in those who originally performed well when no-taping. Screening of ankle proprioception may identify those who would benefit most from taping.